O olhar fantasmagórico : o reaparecimento de uma imagem do rosto e a experiência de alteridade no cinema - Gödecke, Bruno Carboni (2020)
The present work seeks to understand the reappearance of a similar image in the filmographies of Jean Epstein, Robert Bresson, Bruno Dumont and Pedro Costa, filmmakers from different periods that cover almost a century of cinematographic art. The image in question is characterized by a face with a fixed gaze that does not explicit the internal emotions of the characters. The work proposes to analyze scenes that contain such an image, based on a theoretical debate on the question of alterity in cinema, articulating the concept through the thought of the philosopher Emmanuel Levinas. The approximation of the images to the theme intends to demonstrate how, in the reappearance of the hantasmagoric gaze in the work of the filmmakers worked on, a search is made explicit both for representing and reflecting this question, as well as for producing an experience of alterity in cinema.